Permeable Boundaries: Interiors- a Field of Possibilities - Lommerse, Marina; Smith, Dianne (John Curtin Gallery, 2010)
This publication supports the exhibition: Permeable Boundaries: Interiors – a field of possibilities 8 April – 30 April : Access Gallery, John Curtin Gallery